Development of a Standardised Scale to Measure Farmers’ Attitude towards Indigenous Cattle Conservation: A Methodological Approach - Salam, SALAM PRABEX; SAIDUR RAHMAN,; Harideep Verma,; Vimla Saran, (Indian Journal of Extension Education, 2025)
The standardized scale was developed to measure farmers' attitudes towards the conservation of indigenous cattle in 2023 in the Bareilly district of Uttar Pradesh state. A total of 55 items were subjected to experts for relevancy testing, and finally, 36 items were selected for item analysis. These 36 items were presented to 42 respondents from other than the study area. The item analysis score was performed using Likert’s rating technique of measurement, and t values were calculated for each item. Finally, 20 items were selected and were standardized by establishing their reliability (split-half method) and validity (content validity). The overall test reliability (using Spearman Brown formula), Cronbach’s alpha value, and overall content validity index were 0.791, 0.829, and 0.930, respectively. Thus, the reliability and validity of the current scale indicate its consistency and precision of the results. The developed scale will help the researchers in assessing the attitude of farmers towards the conservation of indigenous cattle within a defined target population. Additionally, it will facilitate the development of evidence-based extension strategies and programs designed to enhance conservation efforts and sustainable livestock management.